Classification, System and Terms of Sport Wrestling Methods (Texas Journal of Multidisciplinary Studies, 2022)
Dividing different methods of struggle according to their common characteristics (classifications) allows professionals to develop theoretical and practical knowledge about the science and at the same time helps to identify gaps in this knowledge. In wrestling, the athlete's technical movements are different and different from other sports due to their diversity. This article deals with the issues of classification, system and basic terminology of kurash struggle methods. Provides valuable recommendations on learning techniques and the use of kurash terminology